The Properties of Lightweight Aggregates Pre-Coated with Cement Pastes and Their Suitability for Concrete - Lucyna Domagała (MDPI AG, 2021)
One of the biggest technological problems connected with the production of lightweight concretes made of porous aggregates is their much higher water absorption, which may cause on the one hand workability loss, and on the other hand excess water content in concrete. The aim of this research was to assess the effect of impregnation of lightweight aggregates (LWAs) with cement paste on their properties and to verify its effectiveness in concretes. Three types of lightweight aggregates differing in porosity and pore structure (sintered fly ash Lytag, expanded clay: Leca and Liapor) were selected for the tests. The following parameters were taken into consideration in the research program: LWA type and size, LWA initial moisture content, strength, and rheology of cement pastes. The tests of 22 different aggregates, plain and coated with cement paste, included density, crushing strength, and development of water absorption in time. The research program proved that porous aggregates, due to their impregnation with cement pastes, may be effectively sealed and strengthened. All tested LWAs showed a considerable decrease in water absorption by up to 71%. However, only Lytag aggregate showed a visibly enhanced crushing strength. Verification of effectiveness of aggregate sealing on the enhancement of concrete properties showed both a considerable reduction in water absorption of composites (by up to 52%) and a very high increase in their strength (by up to 107%).